1992
DOI: 10.1111/j.1651-2227.1992.tb12089.x
|View full text |Cite
|
Sign up to set email alerts
|

Cushing's syndrome due to primary pigmented nodular adrenocortical disease with cardiac myxomas and mucocutaneous lentigines

Abstract: A young Japanese female demonstrated unusual features of Cushing's syndrome, cardiac myxomas and mucocutaneous lentigines. At the age of 12 years she presented with growth failure and obesity. The dexamethasone suppression test, the metyrapone test and low corticotropin concentrations indicated a primary adrenal disorder. At surgery, the adrenal glands were not enlarged (the right, 4.0 g; the left; 4.5 g) but had numerous small dark brown nodules. The pathological findings showed multiple small black cortical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Close to 200 patients have been reported from diverse ethnic groups, since the initial description of the complex (1,16,17,64,(69)(70)(71)(72). In the late 1980's, investigators reported the presence of "adrenal-stimulating immunoglobulins" leading to corticotropin-independent adrenocortical nodular hyperplasia in affected subjects and suggested that "Carney complex was an inherited disease of immunological origin" (52,73).…”
Section: Discussionmentioning
confidence: 99%
“…Close to 200 patients have been reported from diverse ethnic groups, since the initial description of the complex (1,16,17,64,(69)(70)(71)(72). In the late 1980's, investigators reported the presence of "adrenal-stimulating immunoglobulins" leading to corticotropin-independent adrenocortical nodular hyperplasia in affected subjects and suggested that "Carney complex was an inherited disease of immunological origin" (52,73).…”
Section: Discussionmentioning
confidence: 99%
“…Carney et al 14,15 and others [16][17][18][19][20][21] have described the clinical and pathological features of a syndrome consisting of cardiac myxomas, spotty pigmentation (lentiginosis), and endocrine over activity. One of our cases, a 14-year-old female "familial myxoma" patient, demonstrated signs of cutaneous pigmentation around her lips consistent with Carney complex.…”
Section: Discussionmentioning
confidence: 99%